Thermoelectric device with electronic control unit for diagnostics of inflammatory processes in the human organism - Anatychuk, L. I.; Kobylianskyi, R. R.; Cherkez, R. G.; Konstantynovych, I. A.; Hoshovskyi, V. I.; Tiumentsev, V. A. (Technology and design in electronic equipment, 2017)
The paper presents a thermoelectric device capable of simultaneously measuring the temperature and density of heat fluxes on the surface of a human body with the help of a developed thermoelectric sensor with a thermostated free surface, thus excluding the effect of ambient temperature on the sensor readings. A special computer programme has been developed for processing the measurement results by way of accumulating and reproducing them in a specified form on a personal computer, which enables monitoring the temperature and thermal state of a human in real time. The specific features of the device design and its technical characteristics are given.